Self-interfering high harmonic beam arrays driven by Hermite–Gaussian beams - David D. Schmidt; José Miguel Pablos-Marín; Cameron Clarke; Jonathan Barolak; Nathaniel Westlake; Alba de las Heras; Javier Serrano; Sergei Shevtsov; Peter Kazansky; Daniel Adams; Carlos Hernández-García; Charles G. Durfee (APL Photonics, 2025)
The use of structured light to drive highly nonlinear processes in matter not only enables the imprinting of spatially resolved properties onto short-wavelength radiation but also opens alternative avenues for exploring the dynamics of nonlinear laser–matter interactions. In this work, we experimentally and theoretically explore the unique properties of driving high-order harmonic generation (HHG) with Hermite–Gaussian beams. HHG driven by Laguerre–Gauss modes results in harmonics that inherit the azimuthal Laguerre–Gauss modal structure, with their topological charge scaling according to orbital angular momentum conservation. In contrast, when HHG is driven by Hermite–Gauss beams, the harmonic modes do not show a direct correspondence to the driving modal profile. Our experimental measurements using HG0,1 and HG1,1 modes, which are in excellent agreement with our numerical simulations, show that the lobes of the Hermite–Gauss driving beams effectively produce a set of separate phase-locked harmonic beamlets that can interfere downstream. This self-interference, which can be adjusted through the relative position between the gas target and the driving beam focus, can be exploited for precision extreme-ultraviolet interferometry. We demonstrate a simple application to calibrate the dispersion of an extreme-ultraviolet diffraction grating. In addition, we show through simulations that the array of harmonic beamlets can be used as an illumination source for single-shot extreme-ultraviolet ptychography.